Reflections on educating prospective ELT teachers: Silence and health in Polish and Japanese school settings - Bąk-Średnicka, Anna (Neofilolog, 2024)
In this paper we reflect on patterns of silence related to health within both Polish and Japanese school settings. This study goes beyond the typical perception of silence as a positive or negative phenomenon. While it refers to the utilization of agential silence as a pedagogical and learning tool, expertly employed by teachers, it also draws educators’ attention to the need to raise teacher-candidates’ empathic concern about students’ various reasons for keeping silent. In this sense, the study transcends the understanding of student silence as merely highlighting their low communicative skills, as it may, in fact, indicate they have physical and mental health problems. The present study took a grounded theory approach. The corpora consisted of 320 utterances expressing primary, secondary, and tertiary subjects’ opinions about silence, accessible in studies by Olearczyk (2016) and King (2013). Manual and software-based data analysis identified eight major categories of the meaning of silence. These categories enabled the selection of the core category of silence in relation to health, providing a fuller picture of the silences presented in the two abovementioned studies.